Policy consultancy in comparative perspective patterns, nuances and implications of the contractor state - Berg, Caspar van den 1980-; Howlett, Michael 1955-; Migone, Andrea; Howard, Michael; Pemer, Frida 1974-; Gunter, Helen ca. 20./21. Jh (Cambridge studies in comparative public policy, 2020)
Many Western countries have seen an increase in the volume and importance of external consultants in the public policy process. This book is the first to investigate this phenomenon in a comparative and interdisciplinary way. The analysis shows who these consultants are, how widely and for what reasons they are used in Britain, the United States, Canada, Australia, The Netherlands and Sweden. In doing so, the book addresses the positive and negative implications of high levels of external policy consultancy, including its implications for the nature of the state (transforming into a contractor state?) and for democratically legitimized and accountable decision-making (transforming into consultocracy?). It provides valuable new insights for students and practitioners in the fields of public administration, public policy, public management, political science and human resource management